Utilizing Alumina-Silica Enriched Bricks Debris Determining End Product of ML-CL Fill Soil: Advanced Stabilization Practices with Innovating Discarded Material - Muhammad Afzaal; Ihsanullah Shah; Muhammad Sheraz; Sher Shah; Arif Rashid; Masaud Ahmad Khan; Mateeullah (Journal of ICT, Design, Engineering and Technological Science, 2021)
Testing soil and knowing its strength parameters is one of the basic components in construction. Testing of fill soil is carried out to find whether the existing soil can endure the burden of structure withheld upon it or not. In the case of weak soil, one can find it difficult to pursue construction or any development project. While talking of solutions, there are many methods to improve its strength and properties: one of them which we decided to work on is 'stabilization of fill soil using bricks waste which is normally easily available material. The main objective of our test is to check the effectiveness of bricks waste on the mechanical properties of filling material. The testing comprised of performing Atterberg limits, Unconfined Compression, Direct Shear, Sieve Analysis, Moisture Dry Density, and Permeability. The Bricks waste passing no. 40 sieve is mixed with fill soil and testing on different proportions i.e. 0, 5, 10, 15 and 20 percent was carried out. The summary was prepared showed improvement in soil regarding the shear strength and toughness as the Plasticity Index of the soil was improved. The unconfined compression test results show a pattern in which the peak stress is increased as we move to higher percentages. Also, the moisture content is increased for this test because the brick debris absorbed water. Direct shear test on percentages up to 15% showed that the peak shear stress increased, which indicates that on higher percentages the sample took more load as compared to small percentages. Moisture Dry Density relationship provides a clear indication of an increase in density of soil as moved to higher percentages and decrease in Optimum Moisture Content which suggests that, clay absorbs more water content as compared to brick debris.